2012
DOI: 10.1007/s00401-012-1056-7
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibroma-associated macrophages play roles in tumor growth and response to pharmacological inhibition

Abstract: Neurofibromatosis type 1 (NF1) is a common genetic disease that predisposes 30–50 % of affected individuals to develop plexiform neurofibromas. We found that macrophage infiltration of both mouse and human neurofibromas correlates with disease progression. Macrophages accounted for almost half of neurofibroma cells, leading us to hypothesize that nerve macrophages are inflammatory effectors in neurofibroma development and/or growth. We tested the effects of PLX3397, a dual kit/fms kinase inhibitor that blocks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
127
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(147 citation statements)
references
References 39 publications
(49 reference statements)
7
127
0
6
Order By: Relevance
“…De-Nardo et al (21) noted that the leukocyte composition of established tumors, in which immunosuppressive M2-like TAMs likely predominated over M1 macrophages. Prada et al (22) and Wang et al (23) suggested that incipient tumors, which may be more immunogenic than established lesions, contained higher proportions of M1-like TAMs, which could initiate adaptive immune responses. In the present study, we analyzed the expression of PLD4 in 109 colon cancer specimens during different clinical and pathological grades by IHC.…”
Section: Discussionmentioning
confidence: 99%
“…De-Nardo et al (21) noted that the leukocyte composition of established tumors, in which immunosuppressive M2-like TAMs likely predominated over M1 macrophages. Prada et al (22) and Wang et al (23) suggested that incipient tumors, which may be more immunogenic than established lesions, contained higher proportions of M1-like TAMs, which could initiate adaptive immune responses. In the present study, we analyzed the expression of PLD4 in 109 colon cancer specimens during different clinical and pathological grades by IHC.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of initial data suggests that the macrophages in NF1 tissues are not principally synthetic macrophages (Prada et al 2013), but additional studies are required. Macrophages at an early stage of NF1 are protective against NF1 development, while at late stages macrophages contribute to the severity of neurofibromas (Prada et al 2013). It is currently unclear whether there is a corresponding phenotypic switch from inflammatory M1 macrophages to synthetic M2 macrophages in NF1.…”
Section: Gingival Overgrowth and Cancermentioning
confidence: 99%
“…It is currently unclear whether there is a corresponding phenotypic switch from inflammatory M1 macrophages to synthetic M2 macrophages in NF1. Interactions between inflammatory cells and connective tissue cells leading to proliferative and fibrotic consequences are likely, but still only partially understood (Staser et al 2010;Prada et al 2013). Increased release of TGF-β in particular from mast cells and/or macrophages is suspected as being a driving force in the development of both gingival overgrowth and neurofibromas (Saito et al 1996;Tipton and Dabbous 1998;Ling et al 2005;Yang et al 2006).…”
Section: Gingival Overgrowth and Cancermentioning
confidence: 99%
“…Although infiltration of macrophages correlates with tumor progression, their exact role in neurofibroma tumorigenesis is not well-understood. 17 Finally, fibroblasts are nonepithelial, noninflammatory, and nonvascular cells of the connective tissue responsible for ECM deposition and reorganization. 18 Upon skin injury, the normal wound repair process includes inflammation followed by fibroblast proliferation, re-epithelization, and ECM remodeling.…”
mentioning
confidence: 99%